Can bibliographic data be put directly onto the semantic web? - Yee MM (Information Technology & Libraries, 2009)
This paper is a think piece about the possible future of bibliographic control; it provides a brief introduction to the Semantic Web and defines related terms, and it discusses granularity and structure issues and the lack of standards for the efficient display and indexing of bibliographic data. It is also a report on a work in progress--an experiment in building a Resource Description Framework (RDF) model of more FRBRized cataloging rules than those about to be introduced to the library community (Resource Description and Access) and in creating an RDF data model for the rules. I am now in the process of trying to model my cataloging rules in the form of an RDF model, which can also be inspected at http://myee. bol.ucla.edu/. In the process of doing this, I have discovered a number of areas in which I am not sure that RDF is sophisticated enough yet to deal with our data. This article is an attempt to identify some of those areas and explore whether or not the problems I have encountered are soluble--in other words, whether or not our data might be able to live on the Semantic Web. In this paper, I am focusing on raising the questions about the suitability of RDF to our data that have come up in the course of my work.